To all the boys I've loved before - Han, Jenny (London : Scholastic, 2014)
"Lara Jean writes love letters to all the boys she has loved and then hides them in a hatbox until one day those letters are accidentally sent"--
Lara Jean's love life goes from imaginary to out of control in this heartfelt novel from the "New York Times "bestselling author of The Summer I Turned Pretty series. What if all the crushes you ever had found out how you felt about them...all at once? Lara Jean Song keeps her love letters in a hatbox her mother gave her. They aren't love letters that anyone else wrote for her; these are ones she's written. One for every boy she's ever loved five in all. When she writes, she pours out her heart and soul and says all the things she would never say in real life, because her letters are for her eyes only. Until the day her secret letters are mailed, and suddenly, Lara Jean's love life goes from imaginary to out of control.
"A Junior Library Guild selection"--Jkt. flap.
Sequel: P.S. I still love you.
Ages 12 up.
Keywords: Love -- Fiction; Dating -- Fiction; Sisters -- Fiction